HRM analysis targeting ITS1 and matK loci as potential DNA mini-barcodes for the authentication of Hypericum perforatum and Hypericum androsaemum in herbal infusions. (March 2016) - Costa, Joana; Campos, Bruna; Amaral, Joana S.; Nunes, M. Eugénia; Oliveira, M. Beatriz P.P.; Mafra, Isabel
Abstract: Hypericum species are among the medicinal plants that are being increasingly used due to their reported health benefits. Hypericum perforatum (St. John's wort) is well known for its anti-inflammatory, anti-depressive and anti-viral properties, as well as a healing agent. In Portuguese folk medicine, Hypericum androsaemum (Hipericão do Gerês) is largely used for its hepatic protective and diuretic properties. This work aimed at searching the potential use of two DNA mini-barcode candidates (ITS1 and mat K) for the authentication of H. perforatum and H. androsaemum in herbal infusions. The sequencing results from ITS1 and matK regions were the basis for the development of species-specific PCR and real-time PCR assays coupled to High Resolution Melting (HRM) analysis, as simple approaches for the reliable discrimination of both species. The barcode regions were successful in the species-specific PCR identification of each target. ITS1 region revealed some intra-species variability from sequencing results, which compromises HRM analysis, while mat K showed to be an adequate mini-barcode for the differentiation of both species by real-time PCR coupled to HRM analysis. The assays were effectively applied to commercial herbal infusions, enabling the consistent identification of two labels with non-declared Hypericum species. Highlights: ITS1 and mat K as DNA mini-barcode candidates for Hypericum spp . identification. Differentiation of Hypericum perforatum and Hypericum androsaemum in herbal infusions. Real-time PCR coupled to high resolution melting analysis. Successful applicability in the authentication of herbal infusions.